KAJIAN NUTRISI SINTETIS DAN VARIETAS SELADA (Lactuca sativa.L) PADA HIDROPONIK SISTEM NUTRIENT FILM TECNIQUE ( NFT): hidroponik, konsentrasi, nutrisi, selada, varietas - Pratama Putra, Zuniar Amanza; Ratna Nurhayati, Dewi; Sigit Saputro, Avisema (innofarm, 2025)
Research on "Study of Synthetic Nutrients and Lettuce Varieties (Lactuca sativa.L) in Hydroponic NFT" conducted was  from June 10 to July 26, 2024. Research this  conducted was in Sidoharjo Village, Boyolali District, Boyolali in Regency. Tools and materials used for the research Hydroponic Installation of 2 dim pipes, 20 cm x 35 cm seedling trays, Total dissolved solids, PH down, 1 liter measuring cup, stationery, Knife/Cutter and digital scales. Matt green, green romaine and olga red lettuce seeds from unknown you seed, MAP, MAG-S, Fleg-G, Calnit fertilizers from PT Synthetic Tetap Jaya, rockwool planting media and raw water. Research aims the obtain  appropriate nutrient for concentration  several varieties in lettuce using the hydroponic NFT system, to obtain suitable varieties for the hydroponic NFT system, and to obtain the interaction between varieties and nutrients with the hydroponic NFT system. The research method used the  design split plot 2 of consisting factor treatment,in main plot the varieties and t sub the plot is  concentration.first factor is the variety of lettuce Maat Green, Green Romaine, Olga Red. Second factor in the concentraci of synthetic nutrients (control), 600 part per million nutrients, 800 ppm nutrients, 1000 ppm nutrients. The combination of treatments consisted of 12 combinations and was repeated 3 times. The observation  were data using analyzed Analysis Variance Of (ANOVA), if significantly different the continued with BNJ test at a level of 5%. Concentration  synthetic of fertilizers not did all affeect  observation parameters, top treatment was the romaine lettuce variety and a nutrient concentration of 1000 ppm on the weight of fresh stumps.